Breakdown performance of backfill materials under impulse and ac voltage conditions - Mileo, Vanessa Carolina Laverde (2012)
Earthing means the connection of equipment through a conductor to ground. The soil is composed by many materials, which can be good or poor conductors of electricity. The earth as a whole is considered as a good conductor of electricity. Many electrical systems are prone to the risk of failure as a result of lightning strikes. It requires special arrangements to reduce the risk involved. A proper ground system is fundamental to this regulation. Lightning impulse has a steep upslope and is source of high frequency current. Special ground systems designs are needed and it is called impulse earthing. Nowadays, most engineers use backfill materials to reduce the ground resistance to low values. Backfill materials or additive fillers are used to refill the space in the vicinity of the electrode. They provide a low ground resistance value. The different models which are available such as Liew and Darveniza, Cooray and colleagues, etc., with the aim to take into account the nonlinear effects due to soil ionization, will be mentioned in this research. Basically, they can be classified as the variable geometry approach and the variable soil conductivity approach. This nonlinear behavior is due to the effects of two conduction processes: thermal and soil ionizations. In the thermal process, the temperature of soil increases through the lowenergy absorption produced by the resistive heating. The soil ionization will increase the soil conductivity and reduce its resistivity, causing the resistance of the soil to decrease with increasing current. This research focuses on the behaviour of dry sand, bentonite and cement under impulse and AC voltage conditions. The selections of materials were based on the availability and anticipation of the past research. There are many factors that could influence the experimental results such as weather, moist of the material, material availability, etc. The experiments were carried out at the TNB Research High Voltage Laboratory. For impulse and AC testings, bentonite breakdown in early stages, unlike cement and air gap (impulse testing) and sand (AC conditions). During the alternative voltage testings for sand and bentonite, dust puffing out from the container and fulgurite formations were observed, this peculiarity is due to high temperatures in the backfill materials during soil ionization.